EVALUASI PROGRAM EARLY WARNING ALERT AND RESPON SYSTEM (EWARS) DALAM PELAKSANAAN SURVEILANS KLB KOTA SALATIGA PROVINSI JAWA TENGAH - Nurvita Wikansari Wikansari; Dian Budi Santoso; Dibyo Pramono; Dyah W Widarsih (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2019)
Outbreaks of disease can result in a large increase in morbidity and mortality, have an impact on tourism, economics and social, so there is a need for an Extraordinary Early Response and Response System (EWARS) (Early Warning and Response System). SKDR has been socialized and replicated gradually throughout Indonesia. Salatiga is one of the cities in Central Java Province and has 6 health centers that have been running the EWARS program in early detection of outbreaks but still occur every year. It is necessary to evaluate the EWARS Program at the Salatiga City Health Service.Evaluation was carried out with a descriptive study of analysis, namely evaluating aspects of input, process, output and outcome by interviewing questionnaires to EWARS health center program administrators and Salatiga City Health Service.The problem with input is that officers have multiple tasks ≥2 (67%) and there are no adequate funds. In the process of targeting and planning (50%) and coordination across sectors (33%). At the output, the officer did not send the report on time and in the outcome of the detection of outbreaks as early as possible but there was no epidemiological bulletin to inform public health every week.There are a number of things that need to be addressed in the EWARS program in Salatiga, namely human resources, facilities and infrastructure as well as planning and implementation. There needs to be equal employment, EWARS training for puskesmas officers and municipal health offices so that they can detect and analyze potentially outbreak diseases as early as possible.